Capabilities of Next-Generation Patch Pump: Improved Precision, Instant Occlusion Detection, and Dual-Hormone Therapy. (January 2019) - Payne, Forrest W.; Ledden, Bradley; Lamps, Greg
Insulin pumps allow patients to attain better blood glucose control with more lifestyle flexibility. Their size and cost, however, limit their usefulness. Current CSII pumps are bulky, intrusive, and expensive. SFC Fluidics is addressing these problems by developing a new type of wearable patch pump based on the patented electro-chemiosmotic (ECO) microfluidic pumping technology. This nonmechanical pumping technology allows accurate and precise delivery of very small amounts of insulin and/or other drugs, including concentrated insulin. The pump engine is small and can be made inexpensively from injection molded parts, allowing its use in a disposable or semidisposable pod format. In addition, a single ECO pump engine can be used to deliver two drugs through independent pathways. Other features of SFC Fluidics' pod include latching safety valves that prevent accidental overdosing of insulin due to pressure changes and an instantaneous occlusion sensor that can immediately detect delivery failure at the first missed dose. These features allow for the development of a series of patch pumps that will offer users the benefit of CSII therapy in a more discreet and reliable patch pump form.